Conjugated polyphenols: Investigation of structure-property relationships and complexation with zinc ions. (February 2017) - Sen, Choong Ping; Valiyaveettil, Suresh
Graphical abstract: Highlights: Conjugated polyphenols with trihydroxybenzene side groups are reported. The structure-property relationships of conjugated polyphenols are investigated. Polyphenol structures can be fine-tuned for selective sensing of metal ions. P1(OH)n showed high binding constant (Ksv = 3.73 x 10 5 M −1 ) for zinc ions. Abstract: Conjugated polymers with ion sensing groups have been synthesized and characterized for developing sensors for toxic and explosive chemicals in different media. In this study, three conjugated polyphenols (P1(OH)n –P3(OH)n ) were synthesized using Sonogashira polymerization and structure-property relationships were established. The target conjugated polyphenols exhibited blue-shifts in absorption (up to 50 nm) and emission (up to 15 nm) maxima in THF, and red-shifts in absorption (up to 45 nm) and emission (up to 17 nm) maxima in DMF of the target polyphenols as compared to those of protected polymers (P1 –P3 ). This is attributed to the disruption of polymer conformation owing to the formation of interchain hydrogen bonds between the trihydroxybenzene groups along the polymer backbone.P1(OH)n showed strong interactions with Zn 2+ ions with a red-shift in emission maximum from 475 nm to 535 nm and a high binding constant (Ksv = 3.73 × 10 5 M −1 ). In contrast, P2(OH)n andP3(OH)n exhibited smaller changes in emission maximum upon addition of Zn 2+ ions (Ksv = 0.69 × 10 5 M −1 forP2(OH)n and 0.32 × 10 5 M −1 forP3(OH)n ). The understanding of the structure-property relationships of such polymers helps to develop metal ion sensors with better selectivity and sensitivity in the future.